2019
DOI: 10.1111/jgh.14856
|View full text |Cite
|
Sign up to set email alerts
|

Non‐alcoholic fatty liver disease and the incidence of myocardial infarction: A cohort study

Abstract: Background and Aim: Non-alcoholic fatty liver disease (NAFLD) is a multisystem disease associated with an increased risk of cardiovascular disease (CVD), diabetes, and chronic kidney disease. Indeed, CVD is the most common cause of death in NAFLD patients. This study aimed to evaluate the association between NAFLD and the risk of incident myocardial infarction. Methods: This is a retrospective cohort study involving 111 492 adults over 40 years old without history of CVD, liver disease, or cancer at baseline w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 40 publications
1
63
0
Order By: Relevance
“…This is interesting, considering that hepatic steatosis content is increasingly studied as a surrogate of disease improvement in early stage clinical trials-despite the fact that it was not previously shown to independently affect mortality [5]. Nonetheless, hepatic steatosis is a very useful clinical aspect for several reasons: (1) it can be assessed rapidly and non-invasively by many physicians without specialized training, (2) it predicts the presence and risk to develop metabolic comorbidities, e.g., diabetes type 2 or myocardial infarction [33,34] and (3) in the current study it correlated with LPS and markers of inflammation. Thus, the presence of moderate and severe hepatic steatosis could be a useful indicator to prioritize patients for dietary interventions, focusing on increasing dietary fiber content.…”
Section: Discussionmentioning
confidence: 99%
“…This is interesting, considering that hepatic steatosis content is increasingly studied as a surrogate of disease improvement in early stage clinical trials-despite the fact that it was not previously shown to independently affect mortality [5]. Nonetheless, hepatic steatosis is a very useful clinical aspect for several reasons: (1) it can be assessed rapidly and non-invasively by many physicians without specialized training, (2) it predicts the presence and risk to develop metabolic comorbidities, e.g., diabetes type 2 or myocardial infarction [33,34] and (3) in the current study it correlated with LPS and markers of inflammation. Thus, the presence of moderate and severe hepatic steatosis could be a useful indicator to prioritize patients for dietary interventions, focusing on increasing dietary fiber content.…”
Section: Discussionmentioning
confidence: 99%
“…Data obtained from a cohort of 229 biopsy-proven NAFLD patients who were followed up for a mean 26.4 (range 6-33) years showed that the presence of fatty liver is associated with an increased risk of cardiovascular disease (HR 1.55, p = 0.01), liver cancer (HR 6.55, p = 0.001), infectious diseases (HR 2.71, p = 0.046), and liver cirrhosis (HR 3.2, p = 0.041) [21]. Even before hepatic decompensation occurs, patients with NAFLD suffer from impaired kidney function [22] and an increased incidence of cardiovascular diseases [23]. Hence, NAFL should be addressed clinically as a systemic disease.…”
Section: Pathogenesis Of Nafldmentioning
confidence: 99%
“…It should be highlighted that, despite the established knowledge that NAFLD is associated with increased risk for the development of CVD, two recently published large cohort studies provide contradictory results on the monitoring of these patients: one suggests that NAFLD patients should be closely monitored for CVD disease prevention [17], while the other proposes that cardiovascular risk stratification in NAFLD patients should be made in the same way as in the general population [18]. We also know that cardiovascular evaluation is rather conservative for asymptomatic NAFLD patients, based on current recommendations, unless they feature intermediate or high risk or have progressed to NASH cirrhosis [19].…”
Section: Dimitrios Ioannis Patouliasmentioning
confidence: 99%